1990
DOI: 10.1111/j.1365-2141.1990.tb02656.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet concentrates irradiated with ultraviolet light retain satisfactory in vitro storage characteristics and in vivo survival

Abstract: We have previously reported that platelet concentrates (PC) may be irradiated with ultraviolet light (UVL) in a cryostorage pack such that mixed lymphocyte reactions (MLR) are abolished whilst satisfactory platelet function is retained during subsequent storage using Fenwal PL-1240 containers. We have now studied both platelet structure and function after irradiation in DuPont Stericell bags which are both UV-permeable and biocompatible. The irradiation dosage was 3000 Joules/m2 of UVL at a mean wavelength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 24 publications
3
15
1
Order By: Relevance
“…Pamphilon reported that platelet concentrates (PC) could become non-immunogenic after UVR and after being stored for 5 days in DuPont Stericell containers. Lactate levels, β-thromboglobulin and platelet factor were higher after UV, while glucose levels decreased with an irradiation dose of 3000 J/m 2 at a mean wavelength of 310 nm applied in DuPont Stericell bags [62]. Ultraviolet B (UVB) irradiation of platelet concentrate (PC) accelerated downregulation of CD14 and nonspecifically increased the loss of monocytes by inhibiting the upregulation of ICAM-1 and HLA-DR [63].…”
Section: Mechanisms Of Action Of Ubimentioning
confidence: 99%
“…Pamphilon reported that platelet concentrates (PC) could become non-immunogenic after UVR and after being stored for 5 days in DuPont Stericell containers. Lactate levels, β-thromboglobulin and platelet factor were higher after UV, while glucose levels decreased with an irradiation dose of 3000 J/m 2 at a mean wavelength of 310 nm applied in DuPont Stericell bags [62]. Ultraviolet B (UVB) irradiation of platelet concentrate (PC) accelerated downregulation of CD14 and nonspecifically increased the loss of monocytes by inhibiting the upregulation of ICAM-1 and HLA-DR [63].…”
Section: Mechanisms Of Action Of Ubimentioning
confidence: 99%
“…Lactate levels, beta-thromboglobulin and platelet factor were increased, while glucose levels were decreased with an irradiation dose of 3000 J/m 2 at a mean wavelength of 310 nm in DuPont Stericell bags [55]. Ultraviolet B (UVB) irradiation of platelet concentrate (PCs) accelerated downregulation of CD14 and nonspecifically increased the loss of monocytes by inhibiting the upregulation of ICAM-1 and HLA-DR [56].…”
Section: Mechanisms Of Action Of Ubimentioning
confidence: 99%
“…At appropriate doses of UV-B light, lym phocytes contained in platelet concentrates are affected but platelet func tion remains intact. Prospective, controlled, randomized studies are being conducted to determine whether there is a reduction in the rate of alloimmunization in patients receiving platelet transfusions exposed to UV-B light and red cell transfusions depleted of leukocytes by fi ltration (10,11).…”
Section: Strategies To Reduce Refractorinessmentioning
confidence: 99%